Anti-discrimination private law: drittwirkung and freedom of contract - Vivas Tesón, Inmaculada (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The aim of this paper is to tackle the study of discriminatory situations within private contracting. The attitude of one of the contracting parties towards the personal or social characteristics of the other (such as race, gender, sexual orientation, nationality, religion or health condition) may influence the exercise of the private autonomy that presides over contractual relations, either by preventing the other party from accessing goods and services by refusing to contract or by imposing more onerous conditions on the other party than on a person with different characteristics. European and Spanish anti-discrimination contract law is analysed, as well as the mechanisms of protection against discriminatory treatment.
Keywords: contractual relationships; discrimination; legal protective measures